2020
DOI: 10.1097/ju.0000000000000530
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Prostate Specific Antigen Monitoring after Holmium Laser Enucleation of the Prostate

Abstract: Introduction: Prostate specific antigen (PSA) screening for prostate cancer has recently been challenged due to poor sensitivity. A number of conditions elevate PSA besides prostate cancer with benign prostatic hypertrophy (BPH) being most common. The objective of this study was to assess the positive predictive value (PPV) of PSA and PSA density (PSAD) for prostate cancer risk following Holmium laser enucleation of the prostate (HoLEP). Methods: An institutional IRB-approved database of HoLEP surgeries perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 8 publications
(9 reference statements)
1
15
0
Order By: Relevance
“…The fact that 5-ARIs are negatively correlated with PSA is well explained in literature [37]. In our study, we were able to demonstrate that the decrease in PSA postoperatively was consistent with patients not receiving 5-ARI treatment, which is consistent with previously reported studies [34]. Stoner et al [38] studied that prostate volume returns to pretreatment levels within 12 weeks of 5-ARI discontinuation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The fact that 5-ARIs are negatively correlated with PSA is well explained in literature [37]. In our study, we were able to demonstrate that the decrease in PSA postoperatively was consistent with patients not receiving 5-ARI treatment, which is consistent with previously reported studies [34]. Stoner et al [38] studied that prostate volume returns to pretreatment levels within 12 weeks of 5-ARI discontinuation.…”
Section: Discussionsupporting
confidence: 91%
“…High PSA levels in patients with LUTS are signi cantly associated with BOO, low PSA levels mean that de nite BOO is unlikely [32]. Baten et al [34] have also reported that BOO can be the cause of chronic irritation of the prostate. This can be caused by high detrusor pressure at maximal voiding (PdetQmax).…”
Section: Discussionmentioning
confidence: 99%
“…Based on our findings, we believe that if Pca is not detected on histopathology evaluation after HoLEP and the post‐HoLEP nadir PSA is significantly higher, that patient should be counseled about further evaluation targeted toward early detection of Pca, especially if a complete adenomectomy was performed. In a recent publication, patients diagnosed with Pca during follow‐up period post‐HoLEP had a higher median PSA at first post‐HoLEP follow‐up compared with those who did not undergo prostate biopsy (1.6 vs 0.68) 9 . Authors noted that patients with a post‐HoLEP PSA above 1 ng/mL had a 94% probability of cancer detection and an 80% risk of clinically significant disease and hence recommended prostatic biopsy for all men with post‐HoLEP PSA above 1 ng/dL 9 .…”
Section: Discussionmentioning
confidence: 97%
“…6 Recent studies also recommend prostatic biopsy for all patients with post-HoLEP PSA above 1 ng/dL. 9 If one attempts to calculate an expected nadir level of PSA based on formula of percent reduction, the nadir level will depend on preoperative baseline PSA. Additionally, it is well known that the baseline PSA is influenced by prostate size, urinary retention status, urinary infection, and presence of prostatitis or incidental Pca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation